Assessment of heavy metal pollution in groundwater of an industrial area: a case study from Ramgarh, Jharkhand, India. Issue 18 (28th December 2022) - Kumar, Suresh; Toppo, Sunil; Kumar, Aneesh; Tewari, Geeta; Beck, Atul; Bachan, Vijeta; Singh, T.B.N.
ABSTRACT: In the present study, pollution evaluation indices were carried out to assess the intensity of pollution in Marar industrial area of Ramgarh in Jharkhand. Fifteen groundwater samples were collected from the study area in May 2016. The physicochemical parameters (pH and EC, , HCO3 −, Cl −, SO4 2-, NO3 −, F −, Ca 2+, Mg 2+, Na +, K + ) and heavy metals (Fe, Mn, As, Zn, Cu, Cr, Ni, Se, Al, Ba, Pb and Cd) were analysed. Measured concentration of heavy metals in the study area in decreasing order is as follows: Fe> Zn> Mn > Al> Ba > Ni> Cu > Pb> Cr > Se> As > Cd. Fe concentration was found beyond desirable limit in each sample. In the study area 73%, 60% and 21% water samples surpass desirable limit of Al, Mn and Ni respectively as per BIS, 10, 500 (2012). Concentration of As, Cu, Cr, Se, Pb, Ba and Cd was within the desirable limit in each sample. The analysed data was then applied for the calculation of Heavy Metal Pollution Index (HPI), Heavy Metal Evaluation Index (HEI) and Degree of Contamination (Cd ). HPI values have not surpassed the critical value of 100 in any of the sample despite of various industrial activities. Fe is the prominent contributor for all the three pollution indices followed by Ni, Cr, Pb, Cu and Mn. According to multiple of mean value approach 100%, 93% and 80% of the samples belong to low and medium classes of HEI, HPI, and Cd respectively. Cluster analysis results advocate that heavy metal concentration in groundwater resources are contributed by both lithogenic as well as anthropogenic inputs such as large number of ferro alloys, non-ferrous alloys, sponge iron, foundry, instrument manufacturing and welding industries in the study area.